IMPACT OF ENTREPRENEURIAL COMPETENCE ON VENTURE PERFORMANCE: THE MODERATING ROLE OF ENTREPRENEURIAL EDUCATION - Afsar Ali; Rauf, Tazein; Ahmad, Nassar; Naveeda (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study investigates the impact of entrepreneurial competence on venture performance, with a particular focus on the moderating role of entrepreneurial education. Despite extensive research on factors influencing venture success, the interplay between entrepreneurial skills and education remains underexplored. This empirical study aims to fill this gap by examining how entrepreneurial education enhances the relationship between entrepreneurial competence and venture performance. Using a quantitative research design, data was collected from 212 entrepreneurs across various MSMEs industries across J&K UT. Entrepreneurial competence was measured using a comprehensive set of indicators, including innovation, risk-taking, and strategic planning abilities. Venture performance was assessed through financial metrics, market share, and growth rates. Entrepreneurial education was evaluated based on the depth and breadth of formal and informal educational experiences related to entrepreneurship. The findings of the research opened a significant positive relationship between entrepreneurial competence and venture performance (p < 0.01). Further, the analysis demonstrates that entrepreneurial education significantly moderates this relationship, amplifying the positive effects of entrepreneurial competence on venture performance (p < 0.05). Entrepreneurs with higher levels of education exhibited superior venture performance compared to those with lower levels of education, highlighting the critical role of entrepreneurial education in fostering successful ventures. These results underscore the importance of integrating entrepreneurial education into training programs to enhance the competencies of aspiring entrepreneurs. By doing so, educators and policymakers can better support the development of ventures, ultimately contributing to economic growth and innovation. This study given valuable insights for educational people, policymakers, and practitioners to promote entrepreneurial success through targeted educational interventions.